Review of Knee Joint Innervation: Implications for Diagnostic Blocks and Radiofrequency Ablation. Issue 5 (13th August 2019) - Roberts, Shannon L; Stout, Alison; Dreyfuss, Paul
Abstract: Objective: To determine if commonly used knee radiofrequency ablation (RFA) techniques would be able to completely denervate the knee joint. Methods: A comprehensive search of the literature on knee joint innervation was conducted using the databases Medline, Embase, and PubMed from inception through February 1, 2019. Google Scholar was also searched. Data on the origin, number of articular branches, course, distribution, and frequency of each nerve innervating the knee joint were extracted from the included studies and compared in order to identify variations. Results: Twelve studies of anterior knee joint innervation and six studies of posterior knee joint innervation were included. The anterior knee joint was innervated by 10 nerves and further subdivided into two parts (anteromedial and anterolateral) or four quadrants (superomedial, inferomedial, superolateral, and inferolateral) based on innervation patterns; the posterior knee joint was innervated by two or three nerves, most commonly via the popliteal plexus. There is a lack of precise, validated anatomic targets identifiable with fluoroscopy and ultrasound for knee diagnostic blocks and RFA. Only three of the 12 or potentially 13 nerves innervating the knee joint are targeted by commonly used knee RFA techniques. Conclusions: Commonly used knee RFA techniques would not be able to completely denervate the knee joint. It may not be necessary to capture all of the nerves, but only the nerves mediating a patient's pain. Further clinical studies are required to validate specific diagnostic blocks and evaluate clinical outcomes using rigorous diagnostic blocks and anatomically specific knee RFA techniques.